2020
DOI: 10.3389/fneur.2020.00275
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Amyotrophic Lateral Sclerosis Based on Diffusion Tensor Imaging and Support Vector Machine

Abstract: Objectives: White matter (WM) impairments involving both motor and extra-motor areas have been well-documented in amyotrophic lateral sclerosis (ALS). This study tested the potential of diffusion measurements in WM for identifying ALS based on support vector machine (SVM). Methods: Voxel-wise fractional anisotropy (FA) values of diffusion tensor images (DTI) were extracted from 22 ALS patients and 26 healthy controls and served as discrimination features. The revised ALS Functional Rating Scale (ALSFRS-R) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…FA decrease was also found in the corpus callosum, and this shift extended to main motor cortices [98][99][100][101][102][103][104][105][106]. In addition, a decrease in FA in the left corona radiata was shown to have a positive correlation with the ALS Functional Rating Scale-Revised (ALSFRS-R) score [98,[107][108][109]. The ALSFRS-R is a standard tool for evaluating the quality of life of people with ALS.…”
Section: Clinical Application Dti In Alsmentioning
confidence: 93%
“…FA decrease was also found in the corpus callosum, and this shift extended to main motor cortices [98][99][100][101][102][103][104][105][106]. In addition, a decrease in FA in the left corona radiata was shown to have a positive correlation with the ALS Functional Rating Scale-Revised (ALSFRS-R) score [98,[107][108][109]. The ALSFRS-R is a standard tool for evaluating the quality of life of people with ALS.…”
Section: Clinical Application Dti In Alsmentioning
confidence: 93%
“…This is consistent with previous studies that showed widespread structural (but not functional) damage in ALS patients compared with HCs [36,39]. Incorporating the significant differences in SC-FC coupling as features in the SVM model resulted in classification performance with similar or even higher accuracy (72.09-81.40%), sensitivity (72.00-88.00%), and specificity (61.11-94.44%) for distinguishing ALS patients from HCs compared to that obtained in previous studies using other neu-roimaging features [42][43][44][45]. Our findings show that SC-FC coupling may be a valuable neuroimaging marker for ALS.…”
Section: Discussionmentioning
confidence: 73%
“…These findings should be replicated in future multicenter longitudinal datasets. Second, other MRI modalities (e.g., DTI) can also help to identify ALS at the early stage [43]; thus, multimodal neuroimaging combinations should be considered in future research. Third, we did not determine the C9orf72 repeat expansion status of ALS patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Discrimination of NDD patients from controls could be performed by the application of an SVM based on ROI-or TOI-based FA values of previously defined NDD-associated brain structures (AD – Zhang et al, 2011 ; Houria et al, 2022 ; PD – Haller et al, 2012 ; Huang et al, 2023 ; ALS – Chen et al, 2020 ; Kocar et al, 2021 ; Münch et al, 2022 ).…”
Section: Postprocessing-related Contributions To Results Of Dti Studi...mentioning
confidence: 99%